National Health Service Bill : Summary of proposed new service (London : His Majesty's Stationery Office)
1946-03 1946 1940s 19 pages 12 Doctors and the Health Centres 56. As and where the new Health Centres are developed existing doctors in the area will be able, if they wish, to use the consulting rooms and other facilities so provided in place of their present surgeries, so far as they are participating in the new service. Their doing so will not affect the general arrangements already described. 57. Any group of doctors joining in practice from a Health Centre, however, will be encouraged — wherever possible — to enter into a partnership arrangement whereby their joint remuneration within the service is pooled and then divided among them on some agreed basis of apportionment. Supply of drugs, medicines and appliances 58. Those who use the general practitioner service will be entitled to the supply, free of charge, of necessary drugs, medicines and appliances. A charge will be made if appliances have to be prematurely repaired or replaced as a result of carelessness, and if the patient chooses to be supplied with more expensive appliances than those normally supplied he will be expected to meet the additional cost involved. 59. Every properly qualified pharmacist who wishes to join in the new service will have the right to do so. The Executive Council in each area is to draw up and publish a list of pharmacists who join in the service, and patients will be able to obtain their supplies on the prescription of their doctor either from the shops or other premises of a pharmacist or from any Health Centre where dispensing services are provided, as the patient chooses. Drugs, medicines and appliances required for hospital purposes will be supplied as part of the hospital service. 60. Regulations, made in consultation with the professional organisations concerned, will govern the detailed terms and conditions, and rates of remuneration, on which pharmacists participate in the new arrangements. Dental service 61. The arrangements for dental services will be on rather a different basis from the family doctor service. Priority will be given to expectant mothers and young people. This is to be done through the local health authority's maternity and child welfare service (which the Bill expressly provides is to include dental care) and through the school health services under the Education Act, 1944. Outside the priority arrangements there will be a general dental service made available, but there will not at first be any guarantee that all people will be able to obtain full dental care without waiting. Any dentist who wishes to participate in the general dental service will have the right to do so, and the Executive Council in each area will draw up and publish a list of those who undertake to participate in the service. 62. The object will be to develop general dental services in the Health Centres, or corresponding Dental Centres, as much and as quickly as possible. In the Centres it is intended that dentists shall be able to participate either whole-time or part-time and shall be remunerated by appropriate salaries for the amount of time which they give to the new service. Outside the Centres it will be open to anyone to arrange with any dentist in his own surgery who agrees to undertake his or her dental care. The dentist will normally be able to start treatment without further reference and subsequently to submit a claim for payment from public funds. For certain forms of treatment, however, the dentist will submit an estimate of what is required to a new professional body established by the Bill — the Dental Estimates Board. The Board will have branch offices in different parts of the country whose 292/847/4/115